2016
DOI: 10.3906/bot-1503-51
|View full text |Cite
|
Sign up to set email alerts
|

The examinations of achene ultrastructural features of section Acrolophus(Centaurea, Asteraceae) via scanning electron microscopy

Abstract: IntroductionAn important and relatively large genus in the flora of Turkey, Centaurea L. comprises ca. 250 species, currently distributed over Eurasia, especially in Irano-Turanian and Mediterranean regions (Anderberg et al., 2007). Centaurea has one of the highest rates of endemism in Turkey, with 112 endemics among 181 total species, 18 endemics among 32 subspecies, and 16 of the 28 varieties (Uysal, 2012). The genus Centaurea has been subjected to morphological, palynological, and cytotaxonomic studies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Achene morphology is a diagnostic characteristic owing to the variation seen in specific and generic levels; therefore, achene morphology can make a distinction at the interspecific level (Szukala et al, 2019). Previous studies reported that achene micromorphology provides useful characteristics for the delimitation of different plant groups, and several achenes and pappus characteristics, achene shape, achene size, color, surface ornamentation, pappus color, length, and structure were suggested as useful in different taxonomic levels in the Asteraceae family (Bona, 2015; Candan et al, 2016; Özcan & Akıncı, 2019; Şirin et al, 2017). This study supports the utilization of achene micromorphology as a distinctive feature for the identification of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achene morphology is a diagnostic characteristic owing to the variation seen in specific and generic levels; therefore, achene morphology can make a distinction at the interspecific level (Szukala et al, 2019). Previous studies reported that achene micromorphology provides useful characteristics for the delimitation of different plant groups, and several achenes and pappus characteristics, achene shape, achene size, color, surface ornamentation, pappus color, length, and structure were suggested as useful in different taxonomic levels in the Asteraceae family (Bona, 2015; Candan et al, 2016; Özcan & Akıncı, 2019; Şirin et al, 2017). This study supports the utilization of achene micromorphology as a distinctive feature for the identification of species.…”
Section: Discussionmentioning
confidence: 99%
“…Macromorphological achene features of the studied species are traditionally used as diagnostic characteristics (Wagenitz, 1975). Several studies showed that achene micromorphology is also useful for identification and taxonomic delimitation in different genera in Asteraceae (Bona, 2014; Candan et al, 2016; Özbek et al, 2018; Rakizadeh, Attar, & Sotoodeh, 2019; Şirin, Ertuğrul, & Uysal, 2017). The present study aims to provide relevant characteristics of the achene macro‐micromorphology and the data useful for solving taxonomic problems through scanning electron microscopy (SEM) in the studied genera.…”
Section: Introductionmentioning
confidence: 99%
“…Though previous studies support the use of achene surface patterns as diagnostic characters at species and subspecies levels for the genus Centaurea s.l., understanding the importance of these characters at generic and subgeneric levels requires further studies (Uysal et al, 2005;Çelik et al, 2005a, b;Aksoy et al, 2010;Okay and Demir, 2010;Shabestari et al, 2013;Bona, 2014;Candan et al, 2015). With this in mind, this study examines the exomorphic achene characters of 23 taxa belonging to the genera Centaurea, Cyanus, Psephellus and Rhaponticoides in Asteraceae by using light microscope (LM) and scanning electron microscope (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…This genus is among the richest in endemic species (Candan et al, 2016). Turkey is the main genetic center for Centaurea.…”
Section: Introductionmentioning
confidence: 99%